Flood caused by driftwood accumulation at a bridge. Issue 5 (13th November 2017) - Kimura, Nobuaki; Tai, Akira; Hashimoto, Akihiro
Abstract : Purpose: Extreme weather events introduced by climate change have been frequent across the world for the past decade. For example, Takeda City, a mountainous area in the south-western Japan, experienced a severe river flood event caused by the factors of high flow, presence of bridges and driftwood accumulation in July 2012. This study aims to focus on this event (hereafter, Takeda flood) because the unique factors of driftwood and bridges were involved. In the Takeda flood, high flow, driftwood and bridge were the potential key factors that caused the flood. The authors studied to reveal the physical processes of the Takeda flood. Design/methodology/approach: The authors conducted a fundamental laboratory experiment with a miniature bridge, open channel flow and idealized driftwood accumulation. They also performed a numerical simulation by using a smoothed particle hydrodynamics (SPH) method, which can treat fluid as particle elements. This model was chosen because the SPH method is capable of treating a complex flow such as a spray of water around a bridge. Findings: The numerical simulation successfully reproduced the bridge- and driftwood-induced floods of the laboratory experiment. Then, the contribution of the studied key factors to the flood mechanism based on the fluid forces generated by high flow, bridge and driftwood (i.e. pressure distributions) was quantitatively assessed. The results showed that the driftwood accumulation and high flow conditions are potentially important factors that can cause a severe flood like the Takeda flood. Originality/value: Simulated results with high flow conditions may be helpful to consider the countermeasure for future floods under climate change even though the test was simple and fundamental.